Effect of the Y chromosome on plasma high-density lipoprotein-cholesterol levels in Y-chromosome-consomic mouse strains - Suto, Jun-ichi (BioMed Central, 2014)
BACKGROUND: Plasma high-density lipoprotein (HDL)-cholesterol level is a clinically important quantitative phenotype that widely varies among inbred mouse strains. Several genes or loci associated with plasma HDL-cholesterol levels have been identified on autosomes and the X chromosome. In contrast, genes or loci on the Y chromosome have not attracted significant attention hitherto. Therefore, we investigated the effects of the Y chromosome on plasma HDL-cholesterol levels in Y- chromosome-consomic (Y-consomic) mouse strains. FINDINGS: Plasma HDL-cholesterol level data from 16 Y-consomic strains demonstrated that the Y chromosome substitutions significantly altered plasma HDL-cholesterol levels, i.e., variations in the plasma HDL-cholesterol level could be partially explained by Y chromosome genes. We obtained the following results from the genotype data on 30 single nucleotide polymorphisms (SNPs), including nonsynonymous and synonymous SNPs and 9 polymorphisms in Sry: (1) Variation in rs46947134 of Uty was significantly associated with plasma HDL-cholesterol levels. (2) A CAG repeat number polymorphism in Sry was significantly associated with plasma HDL-cholesterol levels. (3) Strains with a certain haplotype of the Mus musculus domesticus-type Y chromosome had significantly lower plasma HDL-cholesterol levels than strains with a certain haplotype of the M. m. musculus-type Y chromosome. CONCLUSIONS: The effect of the Y chromosome on plasma HDL-cholesterol levels was confirmed in the Y-consomic strains. We identified several variants associated with plasma HDL-cholesterol levels. Because the physiological significance of various Y-linked genes remains unclear, the results of this study will provide further insights into the functions of Y-linked genes in lipid metabolism.